Intervención urbanística del reasentamiento Nuevo Veracruz a través de la unidad de planificación del área rural, Gigante (Huila) (2022)
Due to the massive displacement of peasants in the area of influence of the El Quimbo reservoir, and all the causes of this problem, the national government in company with Emgesa, implemented 4 resettlement projects for these peasants, of which emphasis and detail is made of the Montea resettlement, in the Nuevo Veracruz village, located in the rural area of Gigante, this choice arises from the fact that Gigante was the municipality that received the greatest social impacts, such as; economic, cultural and environmental aspects of the construction of this hydroelectric plant. At present Emgesa provides in the new resettlement of Nuevo Veracruz, an urbanization made up of 1 9 singlefamily homes, where problems of basic service s still exist, the lack of necessary equipment for these families and the implementation of spaces that provide job opportunities and improvement to farmers. It is then about presenting an alternative way to formulate the most appropriate proposals in a re search and action process, based on the potentialities of those available resources of this rural community in order to face the rehabilitation of rural habitat in its conception. general and housing in particular.